Analysis Of Perceived Benefit And Perceived Barrier With The Use Of Jkn Kis On Bpjs Participants In The Working Area Of Grabagan Health Center, Grabagan District, Tuban Regency - Febrina Eka Saptaningtyas; Ardi Sebastian (Universitas STRADA Indonesia, 2022)
The UHC program has been implemented in all parts of Indonesia, including in Tuban Regency. Since November 1, 2017 the Regional Government of Tuban Regency. The achievement of Universal Healthy Couverage (UHC) in Tuban Regency until October 2021 still has not met the target of 64.73%with a population of 1,219,609 people and a total membership of 789,440 people.To determine the relationship between perceived benefits and perceived barriers with the use of JKN KIS for BPJS participants in the Grabagan Health Center area, Grabagan District, Tuban Regency.This study uses quantitative methods consisting of survey methods and experimental methods. The analysis used using the Pearson Correlation test with a value of = 0.05.Perceived benefits to the use of JKN KIS BPJS participants in the Grabagan Health Center area, Tuban Regency, the most respondents experienced benefits, namely 354 respondents (90,3%), Perceived barrier to the use of JKN KIS BPJS participants in the Grabagan Health Center area, Tuban Regency, the most respondents experienced a barrier as much as 366 respondents (93,4%), Utilization of JKN KIS on BPJS participants in the Grabagan Health Center area of ​​Tuban Regency, most respondents used JKN KIS, as many as 297 respondents (75.8%) and there is a relationship and mutual influence between perceived benefits and perceived benefits. barrier to the use of JKN KIS for BPJS participants in the Grabagan Health Center area, Grabagan District, Tuban Regency.